DEVELOPING READING AND WRITING SKILL OF THE X APH 2 STUDENTS AT THE ODD SEMESTER IN THE ACADEMIC YEAR OF 2014/2015 FOR THE LEARNING MATERIAL OF EXPRESSING INTENTION BY USING PICTURE STORY AND PICTURE FOR WRITING STORY USING RAFT METHOD (Universitas Negeri Semarang, 2014)
This research’s goal is to identify the students’ ability in analyzing the expression of Intention in Reading text and to analyze the students’ capability in writing the expressions through letters and develop their abilities in Reading through pictures and RAFT method. The data showed that there were only 21 % of students able to identify the expression of Intention and the rest was 17 % able to write correctly in their simple sentences. The expression of intention using will, be going to,, intend to, need, want to had the various use and it made them got confused. This research integrated the Reading and Writing skill. The Reading competence analyzed through 5 M. The researcher then compared the result of both activities in Reading and Writing and analyzed the effectiveness of the response again. The result showed that there was a significant increasing of competence and performance in Reading and Writing . The data analyzed showed that there were 75 % students got development in competence and 25 % students found difficulties in finishing the task.